Conversion in American Philosophy Exploring the Practice of Transformation - Ward, Roger A. (Fordham University Press, 2019)
In this fresh, provocative account of the American philosophical tradition, Roger Ward explores the work of key thinkers through an innovative and counterintuitive lens: religious conversion. From Jonathan Edwards to Cornel West, Ward threads the history of American thought into an extended, multivalent encounter with the religious experience. Looking at Dewey, James, Peirce, Rorty, Corrington, and other thinkers, Ward demonstrates that religious themes have deeply influenced the development of American philosophy.This innovative reading of the American philosophical tradition will be welcomed not only by philosophers, but also by historians and other students of America's religious, intellectual, and cultural legacy.